Evaluation of H-type hypertension prevalence and its influence on the risk of increased carotid intima-media thickness among a high-risk stroke population in Hainan Province, China. Issue 35 (28th August 2020) - Zhou, Feng; Hou, Dan; Wang, Yukai; Yu, Dan
Abstract : Abstract: H-type hypertension, defined as a combination of hypertension and hyperhomocysteinemia (Hhcy), is associated with atherosclerosis and, therefore, increased stroke risk. However, the role of hypertension and Hhcy in high-risk stroke populations has not been studied. The present study investigated the prevalence of H-type hypertension in a high-risk stroke population of Hainan Province, China and to assess possible joint effects between hypertension and Hhcy for increased carotid intima-media thickness (CIMT). In this community-based cross-sectional study, 959 high-risk stroke subjects (age, 65.8 ± 10.8 years; 46.6% men) were recruited from Hainan Province, China. The demographic and clinical characteristics were collected, and blood samples were obtained. Analysis of variance or chi-square tests were performed to compare variates among groups based on both homocysteine levels and blood pressure status. The associations of hypertension and Hhcy with increased CIMT were evaluated through logistic regression. The prevalence of H-type hypertension was 34.8% in this population, with a higher ratio of H-type hypertension in men than in women. Compared with the normotension and normal homocysteine subgroup, the risk of increased CIMT was significantly higher in the subgroup with hypertension and Hhcy (odds ratio [OR] = 2.639; 95% confidence interval [CI], 1.690–4.091) after adjusting for age and sex. Increased CIMT was affected by an additive synergetic interaction between Hhcy and hypertension (synergy index = 1.105). It emphasized the clinical importance of anti-hypertension and lowering Hhcy in the high-risk stroke population.